CERTAIN ANTHROPOMETRIC CHARACTERISTICS OF THE TELVE-YEAR OLDS IN THE TOWN OF NIKŠIĆ - Veselin Jovović (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2007)
At the sample of 117 subjects - twelve-year-old pupils of both sexes, the average height, weight and the circumference of chest, brachium, forearm and upper leg were determined. The research was carried out in the primary school «L. Simonović», located in the central area of the town Nikšić. Based on the results of the research it was determined that basic anthropological features of children of the given age group correlate with the values of the population to which they belong. However, comparative research has shown that the subjects from our sample had somewhat higher average values of the parameters than those subjects of the same age participating in the research carried out some years back both in Nikšić and Podgorica.